1979
DOI: 10.1111/j.1749-6632.1979.tb13137.x
|View full text |Cite
|
Sign up to set email alerts
|

WORLD PCBs MAP: STORAGE AND EFFECTS IN MAN AND HIS BIOLOGIC ENVIRONMENT IN THE 1970s

Abstract: PCB residues are found in biota all over the world. A biologic magnification of PCBs has been demonstrated in the food chain: plankton-fish-fish eating birds. A world map of the PCBs residues in biota and some of their biologic effects are given in this study. The biologic effects of PCBs are varied and may generally be explained by the induction or inhibition of the activity of a large number of enzymes, which upsets quantitatively, normal biochemical processes. Harm to reproduction, growth, development, defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(54 citation statements)
references
References 171 publications
0
54
0
Order By: Relevance
“…These compounds have mostly anthropogenic origins and enter the aquatic environment through wastewater and runoff from terrestrial sources. They are toxic to several groups of organisms, including mammals (reviewed in Vanden Heuvel and Lucier 1993), fish (Peaka1l1975), and marine invertebrates (Wassermann et al 1979). In addition, they are very hydrophobic and accumulate in sediments (Kalmaz and Kalmaz 1979) as well as lipid-rich animal tissues (Ernst et al 1976).…”
Section: Hah Toxicitymentioning
confidence: 99%
“…These compounds have mostly anthropogenic origins and enter the aquatic environment through wastewater and runoff from terrestrial sources. They are toxic to several groups of organisms, including mammals (reviewed in Vanden Heuvel and Lucier 1993), fish (Peaka1l1975), and marine invertebrates (Wassermann et al 1979). In addition, they are very hydrophobic and accumulate in sediments (Kalmaz and Kalmaz 1979) as well as lipid-rich animal tissues (Ernst et al 1976).…”
Section: Hah Toxicitymentioning
confidence: 99%
“…Volatile organic compounds (VOCs) [24], certain halogenated compounds [25], several heavy metals [26][27][28] or xenoestrogens like some polychlorinated biphenyls (PCBs) [29][30][31], organochlorine compounds (pesticides) [32][33] and phthalate esters (PEs) [34] may compromise reproductive male function.…”
Section: Introductionmentioning
confidence: 99%
“…PCBs were first detected in the environment in the midto late-1960s as unidentified peaks that were observed during the gas chromatographic analysis of environmental extracts for DDT and related metabolites and breakdown products (9,10). Subsequent studies have identified PCBs as residues in almost all environmental samples.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have identified PCBs as residues in almost all environmental samples. Early packed-column gas chromatographic analysis of the commercial PCBs and PCB residues from diverse environmental extracts demonstrated the complex composition of these mixtures (8)(9)(10)(11); moreover, recent studies using high-resolution analytical methods have confirmed that commercial PCB mixtures and the PCB residues in environmental extracts are highly complex. Inspection of the chromatograms of PCB residues from environmental extracts and from the commercial mixtures clearly demonstrates that the congener composition of the extracts does not resemble that of any single commercial PCB or their reconstituted mixtures.…”
Section: Introductionmentioning
confidence: 99%